KOMUNIKASI INSTRUKSIONAL PELATIH DALAM MELATIH TEKNIK BERNYANYI PADUAN SUARA CANTABILE PEKANBARU - Monica Novrida H.S; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Choir is a kind of sound art that developed in Indonesia and have many achievements international level. The development of choir in Pekanbaru City also began seen since last five years and with many choir attend national and international choir competitons, one of them is Cantabile Choir Pekanbaru. In choir practice led by conductor who give instruction to the singer with instructional communication. The instruction provided by conductor with purpose teach and develop singing techniques identified in research objectives to see the methods, media and instructional obstacle that occurred in the Cantabile Choir exercises.This research uses qualitative research method with symbolic interaction approach. Informants in this research amounted to seven people with purposive technique. The data collection technique was used by observation, interview and documentation. In order to get data validity in this research, the researcher used the extension of participation and triangulation.The result of this research indicate that instructional communication in Cantabile Choir Pekanbaru singing technique exercises using five methode, training method, demonstration method, solfegio (listening method), imitation method and lecture method accompanied by question and answer. All of these methods are very effective in giving singers an understanding of singing techniques. In conveying the instructions the choach also uses verbal and nonverbal symbols to support his communication process. The media used are audio media, audio visual media, visual media and print media. The media used to help choach to give understanding of singing techniques and audiovisual media is very effective media. The obstacles which happened in instructional communication are the source’s obstacle, the channel’s obstacle and the communicant’s obstacle.Keywords: Art, Choir, Instructional Communication